A rare case of unruptured aneurysm of left coronary sinus of Valsalva accompanied with patent foramen ovale and atrial fibrillation detected after cardiac etiology stroke. (2017) - Hohenforst-Schmidt, Wolfgang; Grapatsas, Konstantinos; Zarogoulidis, Paul; Leivaditis, Vasileios; Kotoulas, Christoforos; Tomos, Periclis; Benhassen, Naim; Tsilogianni, Zoi; Koletsis, Efstratios; Haussmann, Erich; Haussmann, Rainer; Huang, Haidong; et al.
Abstract: We present a rare case of a 74 year old female with unruptured aneurysm of the left coronary sinus of Valsalva accompanied with patent foramen ovale and atrial fibrillation. This rare combination was detected during diagnostics for a cardiac etiology stroke. The left coronary sinus of Valsalva was reconstructed using an autologous pericardial patch, the left atrial appendage closed, left atrial ablation performed with cooled radiofrequency and the patent foramen ovale sutured directly. The patient was dismissed on the 12th postoperative day after having an uncomplicated postoperative course.